2022
DOI: 10.1186/s12864-022-08867-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the T cell receptor (TCR) repertoire of the cynomolgus macaque (Macaca Fascicularis)

Abstract: Background Cynomolgus macaque (Macaca fascicularis) is an attractive animal model for the study of human disease and is extensively used in biomedical research. Cynomolgus macaques share behavioral, physiological, and genomic traits with humans and recapitulate human disease manifestations not observed in other animal species. To improve the use of the cynomolgus macaque model to investigate immune responses, we defined and characterized the T cell receptor (TCR) repertoire. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The (37 family members) super-amplification events of the TRBV12 family in pale spear-nosed bats and the large variation in TRBV gene numbers (30 and 100) among Chiroptera have never been reported in mammals. Because previous studies of primates: humans, rhesus monkeys, and crab-eating monkeys( 29, 38, 39 ),carnivores: cats, dogs, ferrets ( 40-42 ) and three species of camels( 43 ), species of the same order differed very little in TRB loci both in terms of loci structure and number of germline genes. Phylogenetic analysis classified Chiroptera as a sister order to Carnivora, and Artiodactyla ( 44 ), and we found that the distribution of TRBV gene families in the 3 bat species was more similar to that of Artiodactyla, with random and huge duplications.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The (37 family members) super-amplification events of the TRBV12 family in pale spear-nosed bats and the large variation in TRBV gene numbers (30 and 100) among Chiroptera have never been reported in mammals. Because previous studies of primates: humans, rhesus monkeys, and crab-eating monkeys( 29, 38, 39 ),carnivores: cats, dogs, ferrets ( 40-42 ) and three species of camels( 43 ), species of the same order differed very little in TRB loci both in terms of loci structure and number of germline genes. Phylogenetic analysis classified Chiroptera as a sister order to Carnivora, and Artiodactyla ( 44 ), and we found that the distribution of TRBV gene families in the 3 bat species was more similar to that of Artiodactyla, with random and huge duplications.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, massive gene duplication events of the TRBV12 family in P. discolor and considerable variation in TRBV gene numbers among Chiroptera have never been reported in mammals. In comparison, studies of primates( 3133 ), carnivores( 3436 ), and camels( 37 ), have shown minimal differences in TRB loci structure and the number of germline genes among species of the same orders. The distribution and evolutionary direction of TRBV gene families in the three bat species is similar to Artiodactyla, with random and massive replications.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, massive gene duplication events of the TRBV12 family in P. discolor and considerable variation in TRBV gene numbers among Chiroptera have never been reported in mammals. In comparison, studies of primates ( 31 33 ), carnivores ( 34 36 ), and camels ( 37 ) have shown minimal differences in TRB loci structure and the number of germline genes among species of the same orders. The distribution and evolutionary direction of TRBV gene families in the three bat species are similar to Artiodactyla, with random and massive replications.…”
Section: Discussionmentioning
confidence: 97%
“…TCR is highly diverse heterodimers consisting of α and β chains (αβ TCR) expressed by most T cells. The variable regions of TCR α and δ chains are encoded by multiple variable (V) and linked (J) genes, while TCR β and γ chains are encoded by diversity (D) genes ( 15 , 16 ). The V region of TCR (Vα and Vβ) has three hypervariable regions, complementary determination region 1 (CDR1), CDR2 and CDR3, among which CDR3 has the largest variation, which directly determines the specificity and diversity of TCR ( 17 ).…”
Section: Introductionmentioning
confidence: 99%